Síntese e utilização de líquidos iônicos como catalisadores na transformação química de CO2 em carbonato de dimetila - Vieira, Michele Oliveira (2015)
The need for the synthesis improvement resulting in process less aggressive to the environment and the use of reusable raw materials are some of the principles of Green Chemistry. Thus, the goal of this work was to study an alternative route of dimethyl carbonate synthesis from CO2, using the working conditions of a CO2 capture plant for the pre-combustion process. Different ionic liquid imidazolium and pyridine cations combined with the anions [Cl]-, [BF4]-, [PF6]-, and [NTf2]- were tested as catalysts. The characterization of the produced ionic liquid was carried out using infrared spectroscopy with Fourier transform (FTIR) and nuclear magnetic resonance spectroscopy of proton (1H-NMR) confirming that the structure of these materials. The purity was determined by assay of the residual chlorides. For the dimethyl carbonate identification and quantification a gas chromatography equipped with a flame ionization detector (GC-FID) was used.For optimizing synthesis parameters were tested the temperatures of 140 °C and 175 °C and reaction time of 12 h, 24 h and 48 h, as well as changes in the cation of the ionic liquids with addition of branching and decreased of alkyl side chain. Herewith the results of methanol conversion and selectivity for DMC showed that these materials can be used as catalysts, but the use of a drying agent to overpass the thermodynamics barrier of the reaction is critical. The most important anions for this synthesis follow the order [BF4]- > [Cl]- > [PF6]- > [NTf2]- for both cations in DMC synthesis. The methanol conversion is maintained constant for all ILs, but the selectivity for dimethyl carbonate reached 81% when [bmim][BF4] was used as catalyst and the loss of this activity after 5 recycles is 8,5 %.